Evaluation of the efficacy of low-level laser therapy (LLLT) and the microelectric neurostimulation (MENS) in the treatment of myogenic temporomandibular disorders: a randomized clinical trial Avaliação da eficácia do laser de baixa freqüência e do neuroestímulo micro elétrico (MENS) no tratamento das disfunções temporomandibulares miogênicas: um estudo clínico randomizado - Evelyn Mikaela Kogawa; Melissa Thiemi Kato; Carlos Neanes Santos; Paulo César Rodrigues Conti (University of São Paulo, 2005)
OBJECTIVE: The aim of the present study was to evaluate the efficacy of low-level laser therapy (LLLT) and the microelectric neurostimulation (MENS) in the treatment of patients with temporomandibular disorders (TMD). MATERIAL AND METHODS: A sample of 19 individuals presenting with signs and symptoms of myogenic TMD was randomly divided into two groups (I - LLLT and II - MENS). Therapy was done in 10 sessions, three times a week, for one month. Patients were evaluated by the Visual Analogue Scale (VAS), measurement of active range of motion (AROM) and muscle palpation, performed immediately before and 5 minutes after each therapeutic session by a blinded TMD specialist. The ANOVA for repeated measurements and Mann-Whitney tests were used for the statistical analysis. RESULTS: The results showed an increase in maximum mouth opening and a decrease in tenderness to palpation for both groups. The VAS reduced for both groups, although more evident for the laser group (p<0.05). CONCLUSION: Authors concluded that both therapies were effective as part of the TMD treatment, and the cumulative effect may have been responsible for this fact. However, caution is recommended when judging the results due to the self-limiting aspect of musculoskeletal conditions such as TMD. OBJETIVO: Avaliar a efetividade do laser de baixa freqüência e do estímulo muscular microelétrico (MENS) no tratamento de pacientes com disfunções temporomandibulares (DTM). MATERIAL E MÉTODOS: Uma amostra de 19 indivíduos com sinais e sintomas de DTM de origem muscular, foi dividida em dois grupos (I -laser e II - MENS). O tratamento consistiu de 10 sessões, três vezes por semana, durante um mês. Os critérios de avaliação dos pacientes foram: escala de análise visual (EAV), mensuração de abertura máxima bucal e palpação muscular, estes foram avaliados imediatamente antes e 5 minutos após cada sessão terapêutica, num estudo do tipo controlado. Para análise estatística, foram aplicados ANOVA para mensurações repetidas e Mann-Whitney. RESULTADOS: Os resultados demonstraram aumento da abertura bucal máxima e diminuição na sensibilidade à palpação em ambos os grupos e, em relação à EAV, ambos os grupos demonstraram decréscimo, mas houve uma diferença estatisticamente significante entre os grupos, já que o grupo laser apresentou os melhores resultados p<0,05. CONCLUSÃO: Os autores concluíram que as duas terapias foram efetivas como parte do tratamento das DTM, e o efeito cumulativo podem ter sido responsável pela melhora. Porém sugere-se cautela quando se analisam os resultados devido ao aspecto autolimitante das condições músculo-esqueletais como as DTM.